Aeromagnetics of selected continental areas flanking the Indian Ocean : with implications for geological correlation and reassembly of Central Gondwana - Sahu, Bijay Kumar (Department of Geological Sciences, 2014)
Reassembling continental fragments of Gondwana has been a subject of interest to many since almost the beginning of the last century. As a result, the broad relative position of the major continental fragments and their dispersal history is well understood using marine magnetic anomalies, coastline geometry, surface geology and limited geophysics. Uncertainty still prevails in reassembly of central Gondwana fragments flanking the Indian Ocean. This thesis aims at utilising geophysical constraints to corroborate an fine-tune the reconstruction of these fragments supported by geological evidence.